Isolation by genomic subtraction of subspecies-specific DNA probes from Verticillium dahliae - N A Patterson; K F DOBINSON (Fungal Genetics Reports, 1998)
The vascular wilt pathogen Verticillium dahliae Kleb. has a very broad host range, including more than 200 different plant species in 45 families. Most isolates cannot be discriminated morphologically, and reliable, rapid methods for classifying and differentiating strains are needed. We have used a genomic subtraction method to isolate DNA probes that can be used to differentiate V. dahliae isolates and to investigate the genetic variation within this fungal species.